Research in Dance/Movement Therapy: Diverse Global Approaches—The 2019 ADTA International Panel. - Capello, Patricia P. (American Journal of Dance Therapy, 2020)
The 2019 ADTA International Panel focused on the growth of research in dance/movement therapy (DMT) as it reflects the expansion of our unique practice worldwide. Research is vital to our field as we strive to verify and validate the varied modalities and techniques that are used by dance/movement therapists in their specific treatment practices. Any form of research typically starts with a question that leads to a systematic inquiry; the need for evidence-based research in DMT is vital for advancing client care and standards of practice in the diverse global environment of our field. This year's panel with representatives from the Japan, Israel, Canada, and the United States was asked to respond to the following topics of inquiry: How has the international expansion of DMT affected research and practice in your country? How do you envision international collaboration for DMT research? How might this expansion and collaboration meet the need to reshape the field for the diverse demands of 2020 and beyond?